2003
DOI: 10.1118/1.1593635
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis using anatomically realistic coronary tree

Abstract: Plaque rupture with superimposed thrombosis is the main cause of the acute coronary syndromes of unstable angina, myocardial infarction, and sudden death. Endothelial disruption leading to plaque rupture may relate to mechanical fatigue associated with cyclic flexion of plaques. A novel method is proposed to assess stress and strain distribution using the finite element (FE) analysis and in vivo patient-specific dynamic 3D coronary arterial tree reconstruction from cine angiographic images. The local stresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…For both CFD and FEA studies, improved methods for generating (1) geometrically accurate 3D vessel geometry through reconstructions derived from contrast‐enhanced magnetic resonance angiography scans obtained during clinical procedures on patients253 and/or (2) patient‐specific in vivo moving 3D coronary arterial trees from cine angiographic images254 should be utilized. Improved methods for generating geometrically accurate flow domains within a stented region that can then be used in CFD studies should be developed, an example being post‐processing procedures used in conjunction with microfocal X‐ray computed tomography imaging and reconstruction 255…”
Section: Areas/topics For Future Studymentioning
confidence: 99%
“…For both CFD and FEA studies, improved methods for generating (1) geometrically accurate 3D vessel geometry through reconstructions derived from contrast‐enhanced magnetic resonance angiography scans obtained during clinical procedures on patients253 and/or (2) patient‐specific in vivo moving 3D coronary arterial trees from cine angiographic images254 should be utilized. Improved methods for generating geometrically accurate flow domains within a stented region that can then be used in CFD studies should be developed, an example being post‐processing procedures used in conjunction with microfocal X‐ray computed tomography imaging and reconstruction 255…”
Section: Areas/topics For Future Studymentioning
confidence: 99%
“…Two more factors may also contribute to plaque rupture and thrombosis at bifurcation sites. A highly localized circumferential wall stress concentration of approximately nine to 14 times the proximal circumferential wall stress occurs at bifurcation sites [28], which, in addition, undergo a larger deformation during cyclic flexion of the coronary artery, yielding a higher circumferential stress than those further to bifurcations [21]. Second, pulsating flow results in oscillatory and vorticity-stream flow patterns at sites of bifurcations with demonstration of backflow in the presence of even minimal atheromatosis [29].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, our findings indicate that the longer the lesion, the higher the probability of plaque rupture and subsequent thrombosis. In experimental models, it has been demonstrated that the larger lesion length results in higher strain on the plaque cap [21].…”
Section: Discussionmentioning
confidence: 99%
“…Ruptured coronary plaques Katritsis et al 349 circumferential wall stress concentration of approximately 9-14 times the proximal circumferential wall stress occurs at bifurcation sites [20], which, in addition, undergo a larger deformation during cyclic flexion of the coronary artery, yielding a higher circumferential stress [21]. Second, pulsating flow conditions as those of coronary circulation result in oscillatory and vorticity-stream flow patterns at sites of bifurcations, with demonstration of back flow in the presence of even minimal atheromatosis [22].…”
Section: Discussionmentioning
confidence: 99%